On solving the cracked-beam problem by block method - Dosiyev, A. A.; Buranay, S. Cival (John Wiley & Sons Ltd, 2008)
An extremely accurate Solution is obtained for the cracked-beam problem by one-block version of the block method (BM). The obtained numerical results demonstrate the exponential convergence of the BM with respect to the number of quadrature nodes. A simple and high accurate formula to compute the stress intensity factor is given. The comparisons with other high accurate results in the literature have been carried out. Copyright (C) 2007 John Wiley & Sons, Ltd.
Keywords: Laplace equation; singularity; block method; stress intensity factor